Optimization of Substrate and Starter Cell Concentrations for Dibenzothiopene Biodegradation by Indigeneous Marine Bacteria Mauricauda olearia LBF-1-0009, Alcanivorax xenomutants LBF-1-0018, and Stakelama pacifica LBF-1-0031 - Yetti, Elvi; Thontowi, Ahmad; Yopi, Yopi (BRIN, 2017)
Dibenzothiophene (DBT) and its derivatives have been widely used as model organic sulfur compounds in petroleum, included their biodegradation process. The abilities of microorganisms to degrade pollutants are significantly influenced by various factors such as microbial species, nutrients and environmental parameters. In this research, we carried out further study to determine optimal condition for DBT biodegradation regarding with substrate and strains cell concentration by several indigenous marine bacteria from Indonesia. These three isolates were belong to Mauricauda olearia, Alcanivorax xenomutants, and Stakelama pacifica, with homology result 99% each. Optimal dibenzothiophene as substrate reached by all isolates is 100 ppm, while cell concentration or microbial numbers that gave highest growth for all isolates is 20 based on conversion of OD600 nm measurement.